Sleep disturbance after acute coronary syndrome: A longitudinal study over 12 months - von Känel, Roland; Meister-Langraf, Rebecca E.; Zuccarella-Hackl, Claudia; Schiebler, Sarah L. F.; Znoj, Hansjörg; Pazhenkottil, Aju P.; Schmid, Jean-Paul; Barth, Jürgen; Schnyder, Ulrich; Princip, Mary (PLOS ONE, 2022)
Background Sleep disturbance has been associated with poor prognosis in patients with acute coronary syndrome (ACS). This study examined the course of sleep disturbance and associated factors in patients with ACS who were followed for one year. Methods Study participants were 180 patients (mean age 59.6 years, 81.7% men) with ACS admitted to a tertiary hospital to undergo acute coronary intervention. Sleep disturbance was interviewer-assessed at admission (n = 180), at 3 months (n = 146), and at 12 months (n = 101) using the Jenkins Sleep Scale (JSS)-4, with a total of 414 assessments over one year. Random linear mixed regression models were used to evaluate the relationship between sociodemographic factors, cardiac diseases severity, perceived distress during ACS, comorbidities, medication, health behaviors, and sleep disturbance over time. Results At admission, 3 months, and 12 months, 56.7%, 49.3%, and 49.5% of patients, respectively, scored above the mean value for sleep disturbance in the general population (JSS-4 score ≥5). There was a significant decrease in continuous JSS-4 scores over time [estimate (SE) = -0.211 (0.074), p = 0.005]. Female sex [0.526 (0.206), p = 0.012], greater fear of dying [0.074 (0.026), p = 0.004], helplessness during ACS [0.062 (0.029), p = 0.034], and a history of depression [0.422 (0.171), p = 0.015] were independently associated with higher JSS-4 scores over time. Conclusion Despite a decrease from admission to 3 months, sleep disturbance is prevalent in the first year after ACS. Female sex, depression history, and distress during ACS identify patients at increased risk of developing persistent sleep disturbance and may inform interventions to prevent sleep disturbance.